Transition from LibSys to KOHA: A Case Study - Prakash Tripathi, Dhanwantari; Kaur, Sarbinder (Journal of Information and Knowledge, 2021)
This paper explains the procedure adopted and the issues encountered in transiting from LibSys to KOHA at the Dr. B. R. Ambedkar National Institute of Technology, Jalandhar. Open Source ILMS KOHA has all the modules required for managing library housekeeping operations. All the data has been successfully migrated from LibSys to KOHA. The paper provides guidelines for transition from LibSys to KOHA.